Liver-related mortality is similar among men and women with cirrhosis - Mazumder, Nikhilesh R (J Hepatol, 2020)
BACKGROUND AND AIMS: Sex-based differences are known to significantly contribute to patient outcomes of chronic disease however the role of patient sex in cirrhosis is unclear. We aim to study the relationship between patient sex and cirrhosis. METHODS: We analyzed a cohort of 20,045 patients with cirrhosis using a Chicago-wide electronic health record database that was linked with the United Network for Organ Sharing (UNOS) and the state death registry cause of death data. Adjusted Cox survival analyses and competing risk analyses were performed to obtain sub-distribution hazard ratios for liver-related cause of death. RESULTS: Female and male patients had similar age, racial distribution, insurance status, and comorbidity status by Elixhauser score. Females had high rates of cholestatic liver disease (17.1% vs 6.2%, p<0.001) and NASH (29.8% vs 21.2% p<0.001) than males. They were less likely to have portal hypertensive complications and had lower peak MELD-Na scores during follow up. Female sex was associated with a decreased hazard of all-cause mortality (aHR 0.85, 95% CI [0.80–0.90]). This effect was attenuated when liver-related mortality was examined (sHR 0.93 95% CI [0.87, 1.00]). No significant difference was noted for women who were ‘ever listed’ in competing risk analyses for either all-cause mortality (sHR 1.09, 95% CI [0.88, 1.35]) or liver-related death (sHR 1.12 95% CI [0.87, 1.43]) despite lower rates of listing (7.5% vs 9.8%, p<0.001) and transplant (3.5% vs 5.2%, p<0.001). CONCLUSIONS: In this longitudinal study of patients with cirrhosis, female sex was associated with a survival advantage likely driven by lower rates of non-liver related death. Women had no difference in risk of liver related death despite lower rates of listing and transplantation.